The great debate : Edmund Burke, Thomas Paine, and the birth of right and left - Levin, Yuval (New York : Basic Books, 2014)
"In The Great Debate Yuval Levin explores the origins of the familiar left/right divide in American politics by examining the views of the men who best represent each side of that debate: Edmund Burke and Thomas Paine. In a groundbreaking exploration of the origins of our political order, Levin shows that our political divide did not originate (as many historians argue) in the French Revolution, but rather in the Anglo-American debate about that revolution. Burke and Paine were both utterly fascinating figures--active in politics, versed in philosophy, and two of the best, most effective and powerful political writers and polemicists in the history of the English speaking world. Levin sets the work of these two men against the dramatic history of their era and shows how they mixed theory and practice to advance their very different notions of liberty, equality, nature, history, reason, revolution, and reform. Paine believed in radical change and saw the American and French Revolutions as catalysts for creating a new society; Burke believed in a significantly more gradual approach with each generation acting merely as part of a long chain of history. These differing approaches to revolution and reform created a division that continues to shape our current political discourse--including issues ranging from gun control and abortion to welfare and economic reform"--
Two lives in the arena -- Nature and history -- Justice and order -- Choice and obligation -- Reason and prescription -- Revolution and reform -- Generations and the living -- Conclusion.
Includes bibliographical references (pages 259-266) and index.
Keywords: Burke, Edmund, -- 1729-1797 -- Political and social views; Paine, Thomas, -- 1737-1809 -- Political and social views; Burke, Edmund -- Political and social views; Paine, Thomas -- Political and social views; Burke, Edmund, -- 1729-1797; Paine, Thomas, -- 1737-1809; Burke, Edmund, -- 1729-1797.; Paine, Thomas, -- 1737-1809.; United States -- Politics and government; Right and left (Political science); Political science -- Philosophy; HISTORY -- Modern -- 18th Century; BIOGRAPHY & AUTOBIOGRAPHY -- Historical; POLITICAL SCIENCE -- Political Process -- General; BIOGRAPHY & AUTOBIOGRAPHY -- Historical; HISTORY -- Modern; Political science -- Philosophy; Right and left (Political science); United States -- Politics and government; Political and social views; Politics and government; Political science -- Philosophy; Right and left (Political science); United States